The post-entry performance of cohorts of export starters in German manufacturing industries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2010)
This paper investigates four cohorts of firms from German manufacturing industries that started to export in the years between 1998 and 2002 and follows them over the five years after the start. Export starters are a rare species and they are small on average compared to incumbent exporters. Between 30 percent and 40 percent of the starters became continuous exporters; some starters stepped out and back into exporting, many of them more than once. The share of total exports contributed by export starters of a cohort is tiny in the start year, and it remains so over the years to follow, although those starters that were exporters in year t+5 had a share of exports in total sales that was more than twice as high as the average share of exports in total sales among the export starters of the same cohort in year t. Contrary to the market selection hypothesis there is no evidence that productivity in the start year is systematically related to survival in the export market. There is no evidence for a negative impact of a smaller firm size in the start year on the chance to survive on the export market. Starting with a higher share of exports in total sales, however, tends to increase the probability to stay on the export market.
Keywords: F14; 330; export starters; post-entry performance; Germany; enterprise panel data; Exportindustrie; Unternehmensgründung; Unternehmensentwicklung; Schätzung; Deutschland